Standards Of Preparation For The Formation Of Social Activity Among Future Primary School Teachers - Tojiddin Zayniddinov (Euro Asian Journal Publishing, 2024)
This article describes the scientific-theoretical, pedagogicalpsychological standards for the formation of social activity skills in primary school students on pedagogical research
Keywords: primary school students; students; legal documents in the field of education; components